2023
DOI: 10.1111/acem.14645
|View full text |Cite
|
Sign up to set email alerts
|

A census of clinical trials conducted under theU.S.exception from informed consent rule

Abstract: Background:The exception from informed consent (EFIC) rule was adopted in 1996, permitting waiver of informed consent for certain emergency research, including trials funded by the U.S. government. The rule requires prospective consent from patients or their legally authorized representative(s) (LAR) if practicable. For those enrolled without consent, the patient or their LAR must be given an opportunity to opt out from continued participation at the earliest opportunity. We sought to census the trials conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
(63 reference statements)
0
0
0
Order By: Relevance
“…The concerns identified in our study, including fear of adverse side effects and loss of parental autonomy, have been reported in previous studies. 11,26,44 Our study found that support for PediDOSE varied by race and ethnicity, health care occupation status, and whether the respondent knew someone with a history of seizures. Previous systematic reviews have had inconsistent results when analyzing the impact of demographic factors on support for EFIC trials, with many individual studies not reporting respondent demographics.…”
Section: Theme 3: Legal and Ethical Concerns About Enrolling Without ...mentioning
confidence: 70%
See 4 more Smart Citations
“…The concerns identified in our study, including fear of adverse side effects and loss of parental autonomy, have been reported in previous studies. 11,26,44 Our study found that support for PediDOSE varied by race and ethnicity, health care occupation status, and whether the respondent knew someone with a history of seizures. Previous systematic reviews have had inconsistent results when analyzing the impact of demographic factors on support for EFIC trials, with many individual studies not reporting respondent demographics.…”
Section: Theme 3: Legal and Ethical Concerns About Enrolling Without ...mentioning
confidence: 70%
“…10 To date, 110 studies have been conducted using EFIC, of which 43 involve prehospital interventions. 11 Studies conducted using EFIC must meet specific criteria and focus on a life-threatening emergent condition where there is no feasible way to obtain prospective consent (Table 1). 10 As part of FDA EFIC regulations, investigators must conduct community consultation to facilitate understanding and promote trust and protection of research participants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations